Analysis of Investor Behavior Types in Choosing Capital Market Investment Preferences in Indonesia - Muhamad Alfin Yudhistira; Zuliani Dalimunthe (Green Publisher Indonesia, 2025)
The increasing number of retail investors and advances in the digitalization of investment services have driven significant growth in the Indonesian capital market. The proliferation of digital investment platforms and rising retail investor participation have notably transformed the landscape of the Indonesian capital market. Understanding investor behavior types and their investment preferences is crucial for market development and regulatory policy formulation. This research aims to identify investor behavior types based on the Behavioral Investor Types framework and analyze their influence on investment style preferences using Social Network Analysis (SNA) and statistical testing methods. The researcher identified investor behavior types based on four Behavioral Investor Types, namely Preserver, Follower, Independent, and Accumulator, and analyzed their influence on investment style preferences, specifically Capital Gain or Dividend, using a Social Network Analysis (SNA) approach and statistical tests. SNA visualization revealed that Independent investors (58.3%) constitute the majority, followed by Preserver (18.1%), Follower (14.6%), and Accumulator (13.1%) types. Most investors prefer Capital Gain over Dividend investment strategies. Statistical analysis showed that only the Accumulator type significantly affects investment style preferences (p = 0.048), while other investor types showed no significant relationship. This research contributes to the development of behavioral finance literature and can serve as a strategic reference for investors, securities companies, and capital market regulators.